PENGARUH JUMLAH PERBANDINGAN INDUK BETINA DAN JANTAN TERHADAP KEBERHASILAN DALAM PEMIJAHAN IKAN KOMET (CARASSIUS AURATUS): Influence Of Is Amount Of Comparison Of Masculine And Female Mains To Efficacy In Spaw Fish Comet (Carassius auratus) - Lojaniadi, Lojaniadi; Rahmawati, Aryani; Sumahiradewi, Luh Gede; Nufus, Chairun (Yayasan Al-Amin Qalbu, 2024)
Intention of this research is to know influence of is amount of comparis on of masculine and female mains to efficacy in spaw of comet fish (Carassius auratus) and to know best comparison in spaw of comet fish (Carassius auratus). Method Research the used is experiment method through to with refer to attempt of device. From result of research of usage of comparison two masculine mains and one female mains tail give result of larva which at most that is mean 1.805,63 tail with Hatching Rate ( HR) 87,99% , While most of sedikt there are at usage of comparison one masculine mains and one female mains yield slimmer that is mean 1.267,39 tail with Hatching Rate ( HR) 72,38%